Effect of Antioxidant and Lipid Profile on the Coronary Heart Disease - Ahmad, Salman A; Al-Sayed, Raghda S (Al-Nahrain Journal of Science, 2018)
Despite the declining coronary heart disease (CHD) mortality rate, CHD remains a major cause of premature death. The present study connect the relationship between SOD (antioxidant enzyme), Lipid profile, Angina and Myocardial Infarction. To achieve this, collected 105 of patient with Angina and MI aged between (38-82) years, then measurement of superoxide dismutase (SOD) activity in sera of patients with Angina and MI. The results indicated moderated significant decreases of SOD levels (p<0.05) in patient when compared with the control group. The degree inhibition of SOD enzyme with various concentration of cyanide, Hydrogen peroxide and diethyl dithiocarbamate, the results recorded that decrease more than 50% of SOD activity at 30 mM of cyanide ion, is measured, and achieve 50% of inhibition at 40 mM of both H2O2 and DDC, this indicated that SOD enzyme more sensitive to the cyanide ion, measurement of lipid profile in sera of patients with Angina and MI. It was indicated highly significant increases of cholesterol and LDL-c levels (p<0.001), and moderated significant increases of triglycerides (p<0.05) whereas no significant decrease in HDL-c levels when compared with the control group.